STUDI POTENSI DAN PERANCANGAN PLTS APUNG DI DANAU BATUR GUNA MENDUKUNG BALI CLEAN ENERGY - Oswald Mangatur, Christian; Setiawan, I Nyoman; Satya Kumara, I Nyoman (Program Studi Teknik Elektro UNUD, 2023)
The province of Bali has a solar energy potential of 1,254 MW but has only utilized 3.7 MWp up to the year 2020. One of the factors contributing to the slow development of PV in Bali is the need for large land areas for the construction of large-scale PV system. One solution to address the limited land availability for large-scale PV is by utilizing bodies of water through the implementation of floating PV. Lake Batur is the largest lake in Bali and has the potential to serve as a location for floating PV. This research aims to determine the technical potential of floating PV and design a system for floating PV in Lake Batur. With reference to the Lake Batur utilization plan and regulations for the use of floating PV, Lake Batur has a technical potential for floating PV of 76.44 MWp. The design of floating PV in Lake Batur is created with three scenarios. All three scenarios for floating PV show performance ratios within the range of 75-85%. The floating PV system also demonstrates an improvement in performance when compared to ground-mounted PV systems.